First record of the hypoptopomatine genus Eurycheilichthys Reis & Schaefer, 1993 (Siluriformes, Loricariidae) from Argentina - Azpelicueta, María de las Mercedes (2014)
The hypoptopomatine genus Eurycheilichthys was so far considered to be endemic to the South of Brazil. One of its species, E. pantherinus, was described from the upper Uruguay river basin. We inform about the finding of this species within the Garibaldi creek, headwater of the arroyo Yabotí Guazú. This is the first record for Argentina which is found in a tributary of the middle Uruguay river.